2019
DOI: 10.1080/07347332.2019.1634176
|View full text |Cite
|
Sign up to set email alerts
|

Distress among African American and White adults with cancer in Louisiana

Abstract: Purpose/Objectives: Screening for distress is a key priority in cancer care, and African American patients may experience increased distress compared to White patients. However, this question has not yet been addressed in Louisiana. The purpose of the present study was to examine the relationship between African American race and distress at a cancer center in Louisiana.Design/Methods: This was a retrospective study of 1,544 patients who were treated at an academic cancer center in 2015. Extracted data include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…4,48,49,59 Consistent with the previous literature, this study found that the three most common reasons survivors reported feeling distressed were physical symptoms, emotional problems, and practical problems. 48,60 Although consistent with other literature, 61 our finding that nearly a third of non-Hispanic Black survivors declined psychosocial support is concerning because Black cancer survivors experience higher distress 62,63 and have more unmet psychosocial needs than White cancer survivors. 58 It is not clear from our data why survivors decline follow-up support, although stigma around mental illness may contribute and has been found to be higher among people from racial and ethnic minority groups than those from majority groups.…”
Section: Discussionsupporting
confidence: 89%
“…4,48,49,59 Consistent with the previous literature, this study found that the three most common reasons survivors reported feeling distressed were physical symptoms, emotional problems, and practical problems. 48,60 Although consistent with other literature, 61 our finding that nearly a third of non-Hispanic Black survivors declined psychosocial support is concerning because Black cancer survivors experience higher distress 62,63 and have more unmet psychosocial needs than White cancer survivors. 58 It is not clear from our data why survivors decline follow-up support, although stigma around mental illness may contribute and has been found to be higher among people from racial and ethnic minority groups than those from majority groups.…”
Section: Discussionsupporting
confidence: 89%
“… 8 , 11 , 12 , 13 , 14 Several studies compared symptoms during or after chemotherapy by race/ethnicity and found mixed results. 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Symptom assessment timing varied in these studies (eg, during treatment vs later in survivorship), which may explain the inconsistent findings. To our knowledge, no studies have compared differences in patient-reported symptoms before starting chemotherapy.…”
Section: Introductionmentioning
confidence: 93%
“…Many prior studies examining racial disparities and distress suffered from a small sample of AA patients. The DT is a validated tool also used in several other articles such as Perry et al (2020) and Weiss et al (2012), demonstrating reliable and effective results.…”
Section: Strengthsmentioning
confidence: 99%
“…There has been little research on racial or socioeconomic status (SES) disparities of cancer patient distress in the United States. A recent study identified that AA cancer patients had higher odds of high distress compared with non-Hispanic Whites, but the significance disappeared with the multivariable model (Perry et al, 2020). Studies using health-related quality of life (HRQoL) reported AAs had lower mental scores and poorer survival compared with White patients (Belachew et al, 2020; Poghosyan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%